Functional Recovery in Autoimmune Encephalitis: A Prospective Observational Study - Seifert-Held, Thomas; Eberhard, Katharina; Lechner, Christian; Macher, Stefan; Hegen, Harald; Moser, Tobias; Jacob, Gregor Brecl; Puttinger, Gertraud; Topakian, Raffi; Guger, Michael; Kacar, Emrah; Zoche, Lea; et al. (Frontiers in Immunology, 2021)
Background: Prospective observations of functional recovery are lacking in patients with autoimmune encephalitis defined by antibodies against synaptic proteins and neuronal cell surface receptors. Methods: Adult patients with a diagnosis of autoimmune encephalitis were included into a prospective registry. At 3, 6 and 12 months of follow-up, the patients’ modified Rankin Scale (mRS) was obtained. Results: Patients were stratified into three groups according to their antibody (Ab) status: anti-NMDAR-Ab (n=12; group I), anti-LGI1/CASPR2-Ab (n=35; group II), and other antibodies (n=24; group III). A comparably higher proportion of patients in group I received plasma exchange/immunoadsorption and second line immunosuppressive treatments at baseline. A higher proportion of patients in group II presented with seizures. Group III mainly included patients with anti-GABABR-, anti-GAD65- and anti-GlyR-Ab. At baseline, one third of them had cancer. Patients in groups I and III had much higher median mRS scores at 3 months compared to patients in group II. A median mRS of 1 was found at all follow-up time points in group II. Conclusions: The different dynamics in the recovery of patients with certain autoimmune encephalitides have important implications for clinical trials. The high proportion of patients with significant disability at 3 months after diagnosis in groups I and III points to the need for improving treatment options. More distinct scores rather than the mRS are necessary to differentiate potential neurological improvements in patients with anti-LGI1-/CASPR2-encephalitis.